Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41388-021-02095-8
|View full text |Cite
|
Sign up to set email alerts
|

RNA demethylase ALKBH5 promotes tumorigenesis in multiple myeloma via TRAF1-mediated activation of NF-κB and MAPK signaling pathways

Abstract: N6-methyladenosine (m6A), an internal modification in mRNA, plays a critical role in regulating gene expression. Dysregulation of m6A modifiers promotes oncogenesis through enzymatic functions that disrupt the balance between the deposition and removal of m6A modification on critical transcripts. However, the roles of mRNA m6A in multiple myeloma (MM) are poorly understood. The present study showed that RNA demethylase ALKBH5 was overexpressed in MM and associated with a poor prognosis in MM patients. Knocking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…In addition, our study also found an interaction between ELAVL1 and m6A regulators in almost all tumors. Cumulative studies have confirmed that m6A imbalance is closely related to tumors ( 13 16 ). Therefore, we believe that although high expression of ELAVL1 is not the cause of tumorigenesis, it may be one of the key molecules in this process.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, our study also found an interaction between ELAVL1 and m6A regulators in almost all tumors. Cumulative studies have confirmed that m6A imbalance is closely related to tumors ( 13 16 ). Therefore, we believe that although high expression of ELAVL1 is not the cause of tumorigenesis, it may be one of the key molecules in this process.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown that m6A dysregulation is associated with tumorigenesis and cancer progression ( 13 16 ). The expression of multiple m6A regulators, including METTL3, FTO, ALKBH5, and YTHDF3, is significantly changed in different tumors, including lung cancer, osteosarcoma, gastric cancer, melanoma, and cholangiocarcinoma ( 17 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is apparent that m 6 A and its related factors (e.g., FTO) are involved in the progression of MM and provide a potential therapeutic target. Furthermore, ALKBH5 is similarly confirmed to be overexpressed in MM and predicts a worse prognosis for MM patients [ 136 ]. Functionally, the downregulation of ALKBH5 promotes tumor cell death and suppresses the growth of MM cells in vitro, exerting a tumorigenic effect.…”
Section: M 6 a Methylation Modifications And Hematological Malignanciesmentioning
confidence: 99%
“…The FTO and ALKBH5 both belong to the AlkB family. However, the function of m6A modification erasure is independent (He et al, 2021; Qu et al, 2022). FTO and ALKBH5 localize in the nucleus with low expression in the cytoplasm.…”
Section: Composition and Function Of M6a‐related Proteinsmentioning
confidence: 99%